2014
DOI: 10.1111/all.12487
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of peanut allergy in infants of Asian-born parents compared to those of Australian-born parents

Abstract: The high peanut allergy prevalence among infants of Asian-born parents appears to have occurred in a single generation and was not present among infants with parents migrating from other countries, suggesting gene-environment interactions are important. The role of eczema and microbial exposure in food allergy prevention warrants exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 24 publications
(33 reference statements)
4
74
0
1
Order By: Relevance
“…In a recent study, Koplin et al found increased prevalence of peanut allergy among infants with parents born in East Asia when compared with infants who had parents born in Australia or Europe. 132 Notably, Asian-born parents did not exhibit higher prevalence of FA compared with Australian-born parents. The authors speculated that although genetically susceptible, Asians born in Asia do not develop allergies due to protective effects of the environment in their native countries and that since Asian infants born in Australia lack this putative protective umbrella, the deleterious effects of allergy genes would be less restrained.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 90%
“…In a recent study, Koplin et al found increased prevalence of peanut allergy among infants with parents born in East Asia when compared with infants who had parents born in Australia or Europe. 132 Notably, Asian-born parents did not exhibit higher prevalence of FA compared with Australian-born parents. The authors speculated that although genetically susceptible, Asians born in Asia do not develop allergies due to protective effects of the environment in their native countries and that since Asian infants born in Australia lack this putative protective umbrella, the deleterious effects of allergy genes would be less restrained.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 90%
“…7,8 Potential confounders considered in the models were children's age and gender, region of residence, whether child had very low birthweight (<1500 g) (VLBW), whether child lives with any siblings, mother's education level, father's education level and SEIFA. Potential confounders considered in our analysis were factors that have been reported to be associated with allergic disease in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian population-based study of 5276 infants showed higher rates of food allergy in the children of immigrants of Asian origin 35. Peanut allergy was three times more likely among infants with parent/s born in East Asia compared with infants whose parent/s were born in Australia (OR 3.4, 95% CI 2.1 – 5.1).…”
Section: Discussionmentioning
confidence: 99%